Genetic diversity in Brazilian tall coconut populations by microsatellite markers - Ribeiro,Francisco Elias (2013)
The tall coconut palm was introduced in Brazil in 1553, originating from the island of Cape Verde. The aim of the present study was to evaluate the genetic diversity of ten populations of Brazilian tall coconut by 13 microsatellite markers. Samples were collected from 195 individuals of 10 different populations. A total of 68 alleles were detected, with an average of 5.23 alleles per locus. The mean expected and observed heterozygosity value was 0.459 and 0.443, respectively. The number of alleles per population ranged from 36 to 48, with a mean of 40.9 alleles. We observed the formation of two groups, the first formed by the populations of Baía Formosa, Georgino Avelino and São José do Mipibu, and the second by the populations of Japoatã, Pacatuba and Praia do Forte. These results reveal a high level of genetic diversity in the Brazilian populations.